Isolation of a Type 1 Avian Adenovirus (CELO) Mutant Which Was Nonpathogenic for the Chicken Embryo - Yates, Vance J. (1970)
A mutant isolated from plaque purified type 1 avian adenovirus (CELO) differed from the parent virus in embryo pathogenicity and in plaque size.